Face-to-Face Lying: Gender and Motivation to Deceive - Elaad, Eitan; Gonen-Gal, Ye’ela (Frontiers in Psychology, 2022)
Two studies examined gender differences in lying when the truth-telling bias prevailed (study 1) and when inspiring lying and disbelief (study 2). The first study used 156 community participants (91 females) in pairs. First, participants completed the Narcissistic Personality Inventory, the Lie- and Truth Ability Assessment Scale (LTAAS), and the Rational-Experiential Inventory. Then, they participated in a deception game where they performed as senders and receivers of true and false communications. Their goal was to retain as many points as possible according to a payoff matrix that specified the reward they would gain for any possible outcome. Results indicated that males lied more and were more successful lie-tellers than females. In addition, males believed the sender less than females but were not more successful detectors of lies and truths. Higher perceived lie-telling ability, narcissistic features, and experiential thinking style explained males' performance. The second study used one hundred volunteers (40 females) who underwent the same procedure. However, the payoff matrix encouraged lying and disbelief. Results showed again that male participants lied more than females. As to performance, males were more successful lie detectors than females, but there was no truth detection difference. Females did not differ in their success in telling and detecting lies and truths. The inconsistent gender differences in production and detection lies and truths dictate caution in interpreting them.